2019
DOI: 10.1136/jmedgenet-2018-105361
|View full text |Cite
|
Sign up to set email alerts
|

Associations of CDH1 germline variant location and cancer phenotype in families with hereditary diffuse gastric cancer (HDGC)

Abstract: IntroductionHereditary diffuse gastric cancer (HDGC) is a cancer syndrome associated with variants in E-cadherin (CDH1), diffuse gastric cancer and lobular breast cancer. There is considerable heterogeneity in its clinical manifestations. This study aimed to determine associations between CDH1 germline variant status and clinical phenotypes of HDGC.MethodsOne hundred and fifty-two HDGC families, including six previously unreported families, were identified. CDH1 gene-specific guidelines released by the Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
0
23
0
5
Order By: Relevance
“…Although the majority of research on HDGC has focused on the role of upper endoscopic examination, there is limited evidence that there may be an association of colorectal SRCC in patients with germline CDH1 pathogenic variants[1]. More recent work has also speculated that the CDH1 variant location may be an important predictor of colorectal cancer risk[37]. Although based on limited data, enhanced colorectal cancer screening by colonoscopy is recommended for CDH1 carriers with a family history of colon cancer, especially when there is a presence of signet ring cells and/or mucinous features of the cancer[1,17].…”
Section: Efficacy Of Endoscopy In Cdh1 Familiesmentioning
confidence: 99%
“…Although the majority of research on HDGC has focused on the role of upper endoscopic examination, there is limited evidence that there may be an association of colorectal SRCC in patients with germline CDH1 pathogenic variants[1]. More recent work has also speculated that the CDH1 variant location may be an important predictor of colorectal cancer risk[37]. Although based on limited data, enhanced colorectal cancer screening by colonoscopy is recommended for CDH1 carriers with a family history of colon cancer, especially when there is a presence of signet ring cells and/or mucinous features of the cancer[1,17].…”
Section: Efficacy Of Endoscopy In Cdh1 Familiesmentioning
confidence: 99%
“…Loss of function of E-cadherin impairs epithelial cell adhesiveness and contributes to cancer progression and metastasis 16. The germline pathogenic truncating and missense mutations are distributed throughout the entire CDH1 gene, and the V832M mutation is located in exon 16, the cytoplasmic domain of the protein 17. The V832M mutation was first identified in a Japanese HDGC family, and was reported again in a patient with early-onset lobular breast cancer 8,18.…”
Section: Discussionmentioning
confidence: 99%
“…CDH1 germline mutations have been described in about 40% of HDGC families and about 2.3% of sporadic early-onset gastric cancer patients 1. Recently, Lo et al 17 reported that the location and type of germline CDH1 variants are related to the age of cancer onset and risk of concomitant cancer in the HDGC families. However, data on the frequency and clinical characteristics of germline CDH1 mutations in unselected gastric cancer patients are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the absence of E-cadherin at the cellular surface may aid the malignant transformation of cells explaining the different cancer manifestations within the HDGC syndrome. An association between the status of CDH1 germline variants with the loss of the precursor region and clinical phenotypes of HDGC being more virulent has also been demonstrated [ 23 ]. Moreover, in families with truncating CDH1 germline variants affecting the precursor region, an increased probability of colorectal cancer has been evidenced [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…An association between the status of CDH1 germline variants with the loss of the precursor region and clinical phenotypes of HDGC being more virulent has also been demonstrated [ 23 ]. Moreover, in families with truncating CDH1 germline variants affecting the precursor region, an increased probability of colorectal cancer has been evidenced [ 23 ]. In CDH1 germline mutation carriers, the possible explanation for the different intracellular transduction perturbations and variable cancer phenotypes might be the different levels of intracellular signal activation including different p-ERK, p-mTOR, and β-catenin levels or the differences in the truncating CDH1 variants to subject CDH1 mRNA transcripts to nonsense-mediated mRNA decay (NMD) [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%